Manfaat Hasil Penyuluhan Bina Keluarga Balita (Bkb) Dalam Pengasuhan Balita Pada Ibu Petani Di Desa Keboncau Sumedang - Lisniawati, Iis; Achdiani, Yani; Widiaty, Isma (Prodi PKK - Departemen PKK - Universitas Pendidikan Indonesia, 2018)
The research is motivated by the lack of knowledge and skills of farmers mothers about parenting. BKB caders explained that farming families are not applying the results of counseling was carried out in BKB activity in daily life. The purpose of the study to determine the benefits of counseling BKB results in the care of infants in women farmers in the Keboncau Sumedang. The method used in this research using descriptive method with a population BKB active participants in following the extension BKB totaling 76 participants. Sampling technique used is purposive sampling of 33 people with certain considerations that mothers of preschool children (3-5 years), a mother who worked as a farmer, and a mother who participated in BKB. The research instrument used is a checklist with questionnaire technique. The results showed that the benefit of the results of BKB counseling in parenting a toddler in women farmers in general are at a very helpful and useful criteria. Recommendations submitted to BKB cadres to further enhance knowledge and skills regarding BKB programs by exchanging ideas with other cadres and attending seminars related to BKB program and to mothers farmers can be used as a basic idea to further improve the care done to their children especially in development aspect Children according to age of development.